ULAMA'S VIEWS REGARDING THE LAW OF PRESERVING BODIES AS LEARNING MATERIAL (CADAVER) - Anjani, Shena Ravina; Variza, Cindy Rantikal; Gushela, Priska Tiarany; Julia, Regina; Anggraeni, Shelpi; Rasyifa, Zahara; Supriyadi, Tedi; Faozi, Akhmad (Journal Analytica Islamica, 2025)
Embalming a corpse without a clear purpose is prohibited, even forbidden, in Islam, while according to the 2007 MUI fatwa, embalming for educational purposes is permitted. However, some scholars have different views, some reject this practice on the grounds that the corpse must be honored and it is prohibited to damage or change body parts for a long time. Furthermore, there are other opinions that state that they agree and remain permitted as long as it is for a clear purpose. This study aims to determine the law of embalming a corpse according to the views of scholars in Sumedang Regency and Majalengka Regency, existing regulations in Indonesia, and the opinions of health workers and nursing academics. In this study, the data analysis method used is a qualitative field data analysis method with an in-depth interview approach to explore the views of several figures consisting of scholars, health workers and academics in nursing. The results of the study show that religious scholars, health workers, and nursing academics in Sumedang Regency and Majalengka Regency agree and allow the act of preserving corpses for educational purposes, namely as cadavers, because it is considered that this can provide many benefits such as being able to help the greater good, namely to increase knowledge and cure millions of sick people for the development of human knowledge in the world.